Identifying barriers and coping strategies for pre-exposure prophylaxis disclosure: experiences of Ugandan adolescent girls engaged in transactional sex—a qualitative study - Mwima, Simon; Bogart, Laura M.; Neema, Steela; Komo, Richard; Obbo, Stephen (Frontiers in Global Women's Health, 2025)
IntroductionThe disclosure of oral pre-exposure prophylaxis (PrEP) use among adolescent girls engaged in transactional sex in Uganda is a complex process shaped by stigma, fear of judgment, misconceptions, and the threat of violence. This qualitative study explores the strategies these adolescents use to navigate these challenges, drawing on resilience theory and asset-based approaches.MethodsBetween April 2018 and May 2019, cross-sectional semi-structured interviews were conducted with Ugandan adolescent girls aged 18–24 engaged in transactional sex to explore their experiences of PrEP disclosure. Data were analyzed using a thematic network analysis approach, focusing on how participants managed the social and psychological barriers to disclosure.ResultsThe study found that stigma, misconceptions about PrEP, and fear of judgment or violence from clients and families were significant barriers to disclosure. However, adolescent girls employed multiple strategies to navigate these challenges. These included relying on peer support, selective disclosure to trusted individuals, and drawing on personal strength and resilience. Support from healthcare providers and access to youth-friendly health services further helped participants manage the risks associated with PrEP disclosure. Many participants used a combination of these strategies, adapting their approach to different social contexts.ConclusionThis study highlights the complex strategies adolescent girls engaged in transactional sex in Uganda use to disclose PrEP use amidst significant barriers. The findings emphasize the need for targeted interventions that focus on strengthening peer support, enhancing the role of healthcare providers, and creating safe spaces for disclosure. By integrating these strategies into PrEP delivery models, public health efforts can empower these vulnerable populations to disclose and adhere to PrEP more confidently, improving HIV prevention outcomes.